Association between omega-3/6 fatty acids and cholelithiasis: A mendelian randomization study - Sun, Qi; Gao, Ning; Xia, Weiliang (Frontiers in Nutrition, 2022)
Background: Omega-3 and omega-6 may be protective factors for cholelithiasis. However, this relationship has not yet been demonstrated clearly. Therefore, we attempted to identify these causal relationships. Methods: The inverse variance weighting (IVW) method was used as the main method of analysis in this study. Multiple methods of analysis were also used in the repeated methods, including the MR-Egger, weighted median, MR-pleiotropic residual sum (MR-PRESSO), outliers, and maximum likelihood methods. In addition, we used multiple sensitivity analyses to identify the potential pleiotropy. Result: In the discovery stage, the results of the random effect IVW analysis showed that higher omega-3 levels were correlated inversely with the risk of cholelithiasis (β = -0.22, 95% CI [-0.32 to -0.12], P = 1.49×10-5). When the replication analysis was performed using another set of instrumental variables (IVs), the causal relationship between omega-3 fatty acids and cholelithiasis remained stable (β = -0.42, 95% CI [-0.66 to -0.18], P = 5.49×10-4), except for the results obtained using the MR-Egger method, which were not significant. The results of the IVW approach showed that each SD increase in omega-6 levels was associated negatively with the risk of cholelithiasis, both in the discovery (β = -0.21, 95% CI [-0.35 to -0.06], P = 4.37×10-3) and the validation phases (β = -0.21, 95% CI [-0.40 to -0.02], P = 3.44×10-2). Conclusions: The findings of our MR study suggested that both omega-3 and omega-6 are correlated causally with a decreased risk of cholelithiasis